2004
DOI: 10.1023/b:biom.0000029438.97990.c6
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexes of 1,10-phenanthroline-5,6-dione alter the susceptibility of the yeast Candida albicans to Amphotericin B and Miconazole

Abstract: Growth of the pathogenic yeast Candida albicans in sub-MIC (minimum inhibitory concentration) levels of Cu(ClO 4 ) 2 · 6H 2 O and [Cu(phendio) 3 ](ClO 4 ) 2 · 4H 2 O (phendio = 1,10-phenanthroline-5,6-dione) increased the concentration of miconazole and amphotericin B required to achieve the MIC 90 whereas pre-growth in AgClO 4 and [Ag(phendio) 2 ]ClO 4 resulted in a small decrease in the relevant MIC 90 values. The copper complexes reduce the oxygen consumption of C. albicans while the silver complexes increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…Taken together, therefore, the data suggest that caspofungin at concentrations below the MIC causes C. albicans cells to undergo apoptosis but that increasing caspofungin concentrations above the MIC does not further induce programmed cell death responses. Previous studies have shown that several stimuli, including acetic acid (7), hydrogen peroxide (27), 1,10-phenanthroline metal complexes (28), silver-coumarin complexes (17), diallyl disulfide (29), farsenol (26), lactoferrin (30), defensins (31), and the antifungal agent amphotericin B (9), cause C. albicans cells to undergo apoptosis. Our data demonstrate that cell wall stress stemming from inhibition of (1,3)-␤-D-glucan, as caused by caspofungin and Zymolyase (at concentrations Ն0.1 mg/ml), is also a trigger for apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, therefore, the data suggest that caspofungin at concentrations below the MIC causes C. albicans cells to undergo apoptosis but that increasing caspofungin concentrations above the MIC does not further induce programmed cell death responses. Previous studies have shown that several stimuli, including acetic acid (7), hydrogen peroxide (27), 1,10-phenanthroline metal complexes (28), silver-coumarin complexes (17), diallyl disulfide (29), farsenol (26), lactoferrin (30), defensins (31), and the antifungal agent amphotericin B (9), cause C. albicans cells to undergo apoptosis. Our data demonstrate that cell wall stress stemming from inhibition of (1,3)-␤-D-glucan, as caused by caspofungin and Zymolyase (at concentrations Ն0.1 mg/ml), is also a trigger for apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that fungal respiration is aVected when cells are exposed to metal-based drugs (Coyle et al, 2003;Eshwika et al, 2004;McCann et al, 2004). Therefore, the respiration rate of cells exposed to each of the diVerent coumarin-silver complexes was determined.…”
Section: Evect Of Coumarin Derivatives On Cellular Respirationmentioning
confidence: 99%
“…However, some of the latter complexes displayed significantly greater anti-Candida activity compare d to the present complexes. In addition, the present Ag(I) complexes had activities similar to that of the prescription drug, miconazole (MIC 90 against C. albicans = 19 lM [17]). …”
Section: Antimicrobial Activitymentioning
confidence: 58%